Practices and representations: The Portugal of Michel Giacometti - Oliveira, L. T de (E-Journal of Portuguese History, 2021)
Taking already-known aspects of Michel Giacometti’s (1929-1990) work as a starting point, this study addresses the role that different spaces played in his research on Portugal. The aim is to use both quantitative and qualitative analysis to assess the geographical coverage of his work, highlighting his descriptions of the regions, identifying those regions that gave rise to specific recordings, and considering his dedications and support networks. In short, the intention is to characterize a geography of Giacometti’s practices and emotions.